The perks of being a wallflower - Chbosky, Stephen (Pocket Books, 1999)
A tale of adolescence whose hero is Charlie, a high school freshman in Pennsylvania. The novel follows Charlie as he is introduced to love, literature and pot. A debut in fiction by a filmmaker.